2020
DOI: 10.1177/1120672120910375
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the glycemic control on the aqueous humor glucose levels in diabetic patients undergoing elective cataract surgery

Abstract: Purpose: Aqueous humor glucose levels play a role in the anterior segment disorders’ pathophysiology, mainly in diabetics. Our purpose was to evaluate the ratio of aqueous humor glucose levels to blood glucose levels in diabetics and to evaluate the correlation between this ratio and blood glycated hemoglobin (HbA1c) levels. Methods: This prospective study was performed in Sheba Medical Center during 2016–2018. The study included type 2 diabetic patients admitted for elective cataract surgery. Blood glucose le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
3
7
0
2
Order By: Relevance
“… 36 Previous reports have shown a close correlation between glucose concentration in aqueous with the glucose concentration in blood in both humans and rabbits. 23 , 37 , 38 Likewise, the close correlation between interstitial fluid and blood has also been previously shown. 12 , 39 This study compared the time delay for the aqueous and interstitial fluid to respond to acute changes in blood glucose levels.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“… 36 Previous reports have shown a close correlation between glucose concentration in aqueous with the glucose concentration in blood in both humans and rabbits. 23 , 37 , 38 Likewise, the close correlation between interstitial fluid and blood has also been previously shown. 12 , 39 This study compared the time delay for the aqueous and interstitial fluid to respond to acute changes in blood glucose levels.…”
Section: Discussionsupporting
confidence: 63%
“… 40 , 41 , 43 Previous studies have shown a closer correlation of blood glucose with aqueous glucose concentrations in diabetic patients compared to nondiabetic individuals, which was attributed to a breakdown of the blood–ocular barrier in diabetics. 38 Ideally, CGM systems should show a change in the glucose concentration within 10 minutes after the blood glucose levels rise. 44 This can be achieved in interstitial fluid, and the results from this study have shown an equivalent response time in the aqueous of the anterior chamber and an even faster response in the posterior chamber of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…In the short-term effect of hyperglycemia, high aqueous humor glucose level is also reported. [50] On the other hand, HbA1c can reflect ECM (Extracellular matrix) remodeling such as collagen cross-linking in the long-term effect of hyperglycemia. Therefore, there may be inconsistent results in Tables 4 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, age population of the subjects was not deeply considered during the study. A previous study reported that the stronger positive correlation ratio could be seen in older patients [ 30 ]. This matter could also be solved when more subjects are recruited for the study.…”
Section: Discussionmentioning
confidence: 99%